Forest resources and rural livelihoods: the conflict between timber and non-timber forest products in the Congo Basin - Ndoye, O.; Tieguhong, J.C. (2004)
The forests of the Congo Basin are exploited by rural communities and timber companies at different scales to meet various conflicting interests. The forest contributes in several ways to rural livelihoods, but the growing importance of timber exploitation poses a threat to this livelihood's fabric and to the conservation of biodiversity. For example 6% of the top 23 timber species exported from cameroon have important non-timber values to local communities. The paper argues that in the process of forest exploitation, a balanced approach is needed to take into account the interests of both rural communities and timber companies. This will require among other things the development and implementation of sustainable forest management plans by timber companies, exclusion from harvesting of timber species that are important to local communities, compensation of timber companies for compliance with management plans, and the involvement of rural communities in monitoring the activities of timber companies.